Pacific oysters are a sink and a potential source of the eelgrass pathogen, Labyrinthula zosterae - Agnew, M Victoria; Groner, Maya L.; Eisenlord, Morgan E.; Friedman, Carolyn S.; Burge, Colleen (Inter-Research, 2022)
Oyster aquaculture and seagrasses often co-occur and are each vital to the ecological and economic value of coastal ecosystems. Global declines in seagrasses, including Zostera mari - na, have recently been observed in association with multiple factors, including infection with diseases such as seagrass wasting disease (SWD), caused by the protist Labyrinthula zosterae. Protection of seagrasses has led to restrictions on oyster aquaculture due to perceived negative impacts on seagrass beds; however, positive impacts may also occur. An important aquaculture species, the Pacific oyster Crassostrea gigas, can filter L. zosterae from the water, potentially re - ducing pathogen transmission, although oysters may vector infection if they accumulate and re - lease live L. zosterae into the water. We investigated whether oyster presence decreases lesion severity and infection intensity in eelgrass, or acts as a vector of L. zosterae, via laboratory and field experiments. In the laboratory, oysters and eelgrass were exposed to L. zosterae for 24 h and kept at 11°C or 18°C for 13 d. In the field, eelgrass ramets were deployed with and without oysters for 28 d adjacent to eelgrass known to have SWD. In the laboratory experiment, the presence of oysters significantly decreased lesion severity and infection intensity, but oysters previously ex - posed to L. zosterae did transmit the pathogen to naïve eelgrass. Temperature did not affect oyster ability to mitigate SWD; however, increased temperature significantly increased lesion severity. Oysters had no effect on SWD in the field. Further research is needed regarding the potential for oysters to vector L. zosterae and to quantify when oysters reduce SWD in the field.